Fatal landslides in Europe - Haque, U., Blum, P.,da Silva, P. F., Andersen, P., Pilz, J., R. Chalov, S., Malet, J.P., Jemec Auflič, M., Andres, N., Poyiadji, E., Lamas, P.C., Zhang, W., Peshevski, I., G. Pétursson, H., Kurt, T., Dobrev, N., García-Davalillo, J.C., Halkia, M., Ferri, S., Gaprindashvili, G., Engström, J. & Keellings, D. (Springer Berlin Heidelberg, 2016)
Landslides are a major hazard causing human and large economic losses worldwide. However, the quantification of fatalities and casualties is highly underestimated and incomplete, thus, the estimation of landslide risk is rather ambitious. Hence, a spatio-temporal distribution of deadly landslides is presented for 27 European countries over the last 20 years (1995–2014). Catastrophic landslides are widely distributed throughout Europe, however, with a great concentration in mountainous areas. In the studied period, a total of 1370 deaths and 784 injuries were reported resulting from 476 landslides. Turkey showed the highest fatalities with 335. An increasing trend of fatal landslides is observed, with a pronounced number of fatalities in the latest period from 2008 to 2014. The latter are mostly triggered by natural extreme events such as storms (i.e., heavy rainfall), earthquakes, and floods and only minor by human activities, such as mining and excavation works. Average economic loss per year in Europe is approximately 4.7 billion Euros. This study serves as baseline information for further risk mapping by integrating deadly landslide locations, local land use data, and will therefore help countries to protect human lives and property.
Keywords: Landslides, Casualties, Fatalities, Europe, Economic loss